2023
DOI: 10.3389/fphar.2023.1220780
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin eugenol ester ameliorates LPS-induced inflammatory responses in RAW264.7 cells and mice

Xu Liu,
Qi Tao,
Youming Shen
et al.

Abstract: Introduction: Inflammation is a defensive response of the body and the pathological basis of many diseases. However, excessive inflammation and chronic inflammation impair the homeostasis of the organism. Arachidonic acid (AA) has a close relationship with inflammation and is the main mediator of the pro-inflammatory response. Based on the prodrug principle, the new pharmaceutical compound aspirin eugenol ester (AEE) was designed and synthesized. However, the effects of AEE on key enzymes, metabolites and infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 52 publications
(54 reference statements)
2
1
0
Order By: Relevance
“…This would affect the integrity of the intestinal epithelial barrier, suggesting that the decrease in tight junction gene expression caused by LPS stimulation may involve the activation of the COX-2-related signaling pathway. Previous studies have confirmed that AEE can regulate the pathways associated with arachidonic acid metabolism and reduce the expression of COX-2 and other genes (20). Similarly, the data of this study showed that the addition of AEE significantly decreased the mRNA expression of COX-2 and mPGES-1 in the ileum of broilers under LPS-induced immune stress.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This would affect the integrity of the intestinal epithelial barrier, suggesting that the decrease in tight junction gene expression caused by LPS stimulation may involve the activation of the COX-2-related signaling pathway. Previous studies have confirmed that AEE can regulate the pathways associated with arachidonic acid metabolism and reduce the expression of COX-2 and other genes (20). Similarly, the data of this study showed that the addition of AEE significantly decreased the mRNA expression of COX-2 and mPGES-1 in the ileum of broilers under LPS-induced immune stress.…”
Section: Discussionsupporting
confidence: 84%
“…In this study, the expression of ileal inflammatory factor genes in the LPS + AEE group was significantly down-regulated compared with the LPS group, suggesting that AEE had a significant alleviating effect on ileal inflammation in broilers exposed to immune stress. Similar studies have confirmed that AEE shows good anti-inflammatory properties both in vivo and in vitro (20). It can inhibit the formation of LPS-induced inflammatory mediators, and significantly reduce the expression and secretion of inflammatory cytokines such as IL-1β, TNF-α, and IL-6, thus alleviating the inflammatory response (18).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation